2011
DOI: 10.1103/physrevb.84.085202
|View full text |Cite
|
Sign up to set email alerts
|

Optically pumped InP: Nuclear polarization from NMR frequency shifts

Abstract: There are a number of mechanisms that can produce frequency shifts in the NMR spectra of optically pumped semiconductors, including the hyperfine interaction, nuclear dipolar fields, and indirect-or J-couplings. Using optically pumped Fe-doped InP, we explore how to experimentally distinguish the shift mechanisms from one another, and then exploit the shifts to measure the absolute nuclear polarization. Furthermore, we optically pump, using circularly polarized light, at a much lower field (2.35 T) than previo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
10
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 55 publications
2
10
0
Order By: Relevance
“…We have previously shown 7 in semi-insulating InP that this contact mechanism, rather than a direct electron-nucleus dipolar mechanism, 8,10 or coupling of nuclei to conduction electrons, is consistent with the experimental results. In this paper we will present additional evidence of this mechanism.…”
Section: Introductionsupporting
confidence: 81%
See 2 more Smart Citations
“…We have previously shown 7 in semi-insulating InP that this contact mechanism, rather than a direct electron-nucleus dipolar mechanism, 8,10 or coupling of nuclei to conduction electrons, is consistent with the experimental results. In this paper we will present additional evidence of this mechanism.…”
Section: Introductionsupporting
confidence: 81%
“…These two competing effects of local polarization and penetration depth were sorted out by using stray-field NMR imaging (STRAFI) to measure the 31 P OPNMR signal in InP with micron spatial resolution as a function of depth from the surface. 5 These results, as well as our own results, 7 showed that super-bandgap photons are more efficient at generating high local nuclear polarizations than sub-bandgap photons.…”
Section: Introductionsupporting
confidence: 64%
See 1 more Smart Citation
“…In particular, one can imagine creating onionlike patterns in which the polarization successively changes sign or amplitude over concentric layers of predefined thickness. The formation of such mesoscale polarization structures could be monitored via the NMR line shifts created by the concomitant long-range fields 31 or could be imaged directly using MRFM. 29 Because the pitch in these structures is ultimately influenced by the nuclear spin relaxation mechanism, such experiments could serve as a platform for significant applications, including the detection of trapped charges or the spatial characterization of hyperfine interactions.…”
Section: Discussionmentioning
confidence: 99%
“…3 A spin polarization far beyond thermal equilibrium is known as "hyperpolarization." [4][5][6] Indium phosphide (InP) features easy electronic spin hyperpolarization using circular-polarized photons, due to its direct band gap of 1.34 eV at room temperature (RT). 7,8 Thus, InP may be a perfect candidate for opto-spinelectronics.…”
mentioning
confidence: 99%